Modeling Aquatic Food Systems of the Future - Chan, Chin Yee (WorldFish, 2025)
With the increased recognition of its nutritional benefits, demand for aquatic foods has been increasing. According to recent research, it is expected to double by 2050. However, anticipating where and how demand will grow, and what factors might impact aquatic food systems, will determine whether this demand is sustainably met. This is why foresight and modeling are so important. Projecting various scenarios can give policymakers a glimpse into the future, allowing them to act pre-emptively to avoid issues such as food shortages, price hikes and environmental degradation.